Modelo didáctico para la simulación de frecuencias audibles utilizadas en audiometría (2019)
The present work consisted in the realization of a didactic model for the simulation of audible frequencies used in audiometry using the programming language Python, it consisted of making an application to generate audible tones with modulable intensities and frequencies, as well as a graphical interface for the visualization of a audiogram modifiable by the user, which for the case would be an instructor or teacher to be implemented in a classroom using audiovisual media.